Teacher readiness in implementing the Free Learning Learning System at SMK Negeri 4 Medan - Wesley Giankeke SB; Sukarman Purba; Alan Azhar Simbolon; Josef Bintang (Formosa Journal of Applied Sciences, 2023)
This study aims to measure the readiness of teachers in implementing independent learning systems at SMK Negeri 4 Medan. The research sample consisted of 3 teachers at the school. Data collection through observation and interviews shows that teachers at SMK Negeri 4 Medan are ready to implement this new policy. They made preparations with training that provided an understanding of the Independent Curriculum. Although some teachers are familiar with previous learning guidelines and lack experience implementing independent learning, they can overcome these barriers through appropriate support and training. Collaboration between teachers is important in facilitating exchange of experiences and problem solving. With practical experience and adequate self-confidence, teachers can carry out independent learning well.